Construction, Deconstruction or Reconstruction? The Swiss Mythos in Contemporary Literature (KULT_online, 2010)
This volume edited by Jürgen Barkhoff, a native German scholar, and his Irish colleague, Valerie Heffernan, examines the field of tension between the construction and deconstruction of Swiss myths in and through literature. It is a collection of papers that were presented at the conference "The Mythos of Switzerland: On construction and deconstruction of the Swiss in the Present-day" which took place at National University of Ireland Maynooth and at Trinity College, University of Dublin. Germanists from abroad and Swiss authors like Adolf Muschg not only focus in their papers on the constitution of myths but also on the function of several myths in Swiss self-identity and -understanding debates. From a geographical point of view Switzerland is a little country, but there are four languages spoken and several cultures melded, so this country has to be regarded as a special case. Main topics of the volume are, therefore, alongside the mythos of Swiss literature, the mythos of the Alps, and the mythos of the Swiss Confederation, also the mythos of a special case and of multiculturalism, and finally, the mythos of literary counter-discourse and the mythos of Ireland.